2017
DOI: 10.1002/2016jc012478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sea‐ice and biogeochemical processes and storms on under‐ice water fCO2 during the winter‐spring transition in the high Arctic Ocean: Implications for sea‐air CO2 fluxes

Abstract: We performed measurements of carbon dioxide fugacity (fCO2) in the surface water under Arctic sea ice from January to June 2015 during the Norwegian young sea ICE (N‐ICE2015) expedition. Over this period, the ship drifted with four different ice floes and covered the deep Nansen Basin, the slopes north of Svalbard, and the Yermak Plateau. This unique winter‐to‐spring data set includes the first winter‐time under‐ice water fCO2 observations in this region. The observed under‐ice fCO2 ranged between 315 µatm in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 83 publications
(213 reference statements)
7
84
1
Order By: Relevance
“…In Friday Harbor in the glacially formed San Juan Archipelago (Washington, USA), p CO 2 ranged from ~300 to ~1,100 μatm over a 2‐year period, mostly with high positive Δ p CO 2 , suggesting that the sea is a source for atmospheric CO 2 in this area (Murray et al, ). On the other hand, Kongsfjorden and Tempelfjorden Arctic fjords (Svalbard, Norway) appeared to be less variable systems (in terms of the carbonate dynamics and saturation state of Ω Arag ) and they apparently act as CO 2 sink systems (Fransson et al, , ). In the case of the Godthåbsfjord system (SW Greenland), the input of fresh glacial meltwater produces a strong CO 2 uptake giving a net negative CO 2 flux within this fjord system (Meire et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In Friday Harbor in the glacially formed San Juan Archipelago (Washington, USA), p CO 2 ranged from ~300 to ~1,100 μatm over a 2‐year period, mostly with high positive Δ p CO 2 , suggesting that the sea is a source for atmospheric CO 2 in this area (Murray et al, ). On the other hand, Kongsfjorden and Tempelfjorden Arctic fjords (Svalbard, Norway) appeared to be less variable systems (in terms of the carbonate dynamics and saturation state of Ω Arag ) and they apparently act as CO 2 sink systems (Fransson et al, , ). In the case of the Godthåbsfjord system (SW Greenland), the input of fresh glacial meltwater produces a strong CO 2 uptake giving a net negative CO 2 flux within this fjord system (Meire et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The collected time series on sea‐ice physics and biogeochemistry further provided an opportunity to evaluate a state of the art sea‐ice numerical model (Duarte et al, ), showing that physics can be well reproduced given the forcing is realistic, and also giving insights into ice algae dynamics in different types of sea ice. A unique time series quantified the factors that affect surface water CO 2 , showing the importance of transient storm events and ice dynamics for ocean‐atmosphere CO 2 exchange in ice‐covered waters (Fransson et al, ). While Nomura et al () showed that the young new sea ice growing in winter and spring is a source CO 2 to the atmosphere, while in older ice the CO 2 flux is strongly modulated by the snow cover properties.…”
Section: Overview Of Conditions During Experiments and Main Findingsmentioning
confidence: 99%
“…The characteristics of the Arctic ice cover has changed from thick multi-year sea ice to thinner first-or second-year sea ice (e.g., Serreze et al, 2007;Rabe et al, 2009;Granskog et al, 2016;Rösel et al, 2018). As a result of all these changes, surface-water stratification, primary production, carbon export and ocean CO 2 uptake are expected to change (e.g., ACIA, 2005;AMAP, 2013AMAP, , 2018Slagstad et al, 2015;Fransson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%